Action on the social determinants of health: advancing occupational equity and occupational rights/ Ações nos determinantes sociais de saúde: avançando na equidade ocupacional e nos direitos ocupacionais - Hammell, Karen Whalley (Cadernos Brasileiros de Terapia Ocupacional, 2020)
Epidemiologists have sought to focus global attention on the “social determinants of health” - the conditions in which people are born, grow, live, work and age - and on the impact of the inequitable distribution of these determinants on people’s opportunities to be healthy. Evidence demonstrates, unequivocally, that occupation is a determinant of human health and wellbeing. Because inequitable social determinants shape the availability of healthpromoting occupational opportunities, occupational therapists have raised the importance of addressing occupational injustices. However, theoretical scholarship pertaining to occupational justice and occupational injustice has been disproportionately dominated by the culturally-specific perspectives of Anglophone theorists from the Global North. The purpose of this paper is to highlight some of the problems and confusions arising from Anglophone scholarship on occupational injustices; and to highlight the importance of action on the social determinants of health through occupation. Confused definitions of various occupational injustices are unhelpful to practitioners. The occupational therapy profession could actively address the social determinants of occupation through focusing on occupational equity and occupational rights, informed by existing scholarship on human capabilities. Issues of occupational rights, denial of occupational rights (occupational injustices), and of in/equities of occupational opportunities ought to be fundamental issues for the occupational therapy profession, whose most pressing concern should surely be: how can occupational therapists most effectively address the social determinants of occupation such that all people have the capabilities to engage in meaningful occupations that contribute positively to their own well-being and the well-being of their communities, as is their right.